2020
DOI: 10.1371/journal.pone.0233758
|View full text |Cite
|
Sign up to set email alerts
|

How robust is the own-group face recognition bias? Evidence from first- and second-generation East Asian Canadians

Abstract: There is mounting evidence that North Americans are better able to remember faces of targets who belong to the same social group, and this is true even when the social groups are experimentally created. Yet, how Western cultural contexts afford the development of this own group face recognition bias remains unknown. This question is particularly important given that recent findings suggest that first-generation East Asian Canadians do not show this bias. In the current research, we examined the own-group bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A majority of evidence (Hugenberg et al, 2011) showed that social categorization into in-group and out-group was sufficient to elicit the OGB, but a series of studies (Shriver et al, 2008;Van Bavel et al, 2008Ng et al, 2016Ng et al, , 2020Yan et al, 2017;Harrison et al, 2020;Fuller et al, 2021) have continued to report inconsistent results, especially when there were no salient physiognomic features on faces (same-race faces without other categorical diagnostic features). For example, some studies showed equivalent recognition memory for in-group versus out-group faces (Yan et al, 2017 for Chinese populations; Ng et al, 2016Ng et al, , 2020 for first-generation East Asian Canadians; Harrison et al, 2020 andFuller et al, 2021 for United Kingdom populations). In-/out-groups categorized by university membership which was a lack of competitive or rivalrous relationships did not elicit an own-group memory bias (Harrison et al, 2020;Fuller et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A majority of evidence (Hugenberg et al, 2011) showed that social categorization into in-group and out-group was sufficient to elicit the OGB, but a series of studies (Shriver et al, 2008;Van Bavel et al, 2008Ng et al, 2016Ng et al, , 2020Yan et al, 2017;Harrison et al, 2020;Fuller et al, 2021) have continued to report inconsistent results, especially when there were no salient physiognomic features on faces (same-race faces without other categorical diagnostic features). For example, some studies showed equivalent recognition memory for in-group versus out-group faces (Yan et al, 2017 for Chinese populations; Ng et al, 2016Ng et al, , 2020 for first-generation East Asian Canadians; Harrison et al, 2020 andFuller et al, 2021 for United Kingdom populations). In-/out-groups categorized by university membership which was a lack of competitive or rivalrous relationships did not elicit an own-group memory bias (Harrison et al, 2020;Fuller et al, 2021).…”
Section: Introductionmentioning
confidence: 99%